Α‐Asarone, β‐asarone, and γ‐asarone: Current status of toxicological evaluation. Issue 8 (25th November 2020) - Uebel, Thomas; Hermes, Lena; Haupenthal, Sabrina; Müller, Lena; Esselen, Melanie
Abstract: Asarone isomers are naturally occurring in Acorus calamus Linné, Guatteria gaumeri Greenman, and Aniba hostmanniana Nees. These secondary plant metabolites belong to the class of phenylpropenes (phenylpropanoids or alkenylbenzenes). They are further chemically classified into the propenylic trans ‐ and cis ‐isomers α‐asarone and β‐asarone and the allylic γ‐asarone. Flavoring, as well as potentially pharmacologically useful properties, enables the application of asarone isomers in fragrances, food, and traditional phytomedicine not only since their isolation in the 1950s. However, efficacy and safety in humans are still not known. Preclinical evidence has not been systematically studied, and several pharmacological effects have been reported for extracts of Acorus calamus and propenylic asarone isomers. Toxicological data are rare and not critically evaluated altogether in the 21st century yet. Therefore, within this review, available toxicological data of asarone isomers were assessed in detail. This assessment revealed that cardiotoxicity, hepatotoxicity, reproductive toxicity, and mutagenicity as well as carcinogenicity were described for propenylic asarone isomers with varying levels of reliability. The toxicodynamic profile of γ‐asarone is unknown except for mutagenicity. Based on the estimated daily exposure and reported adverse effects, officials restricted or published recommendations for the use of β‐asarone and preparations of Acorus calamus . In contrast, α‐asarone and γ‐asarone were not directly addressed due to a limited data situation. Abstract : Asarone isomers are active ingredients of Acorus calamus and are most commonly found in food and traditional herbal medicine. Propenylic asarone isomers are associated with carcinogenic potential in rodents, but mechanistic insights are rare and additional data on basic toxicological effects are limited. Closing data gaps and ensuring a trustworthy data situation is of high importance to gain a better understanding of the compound class of phenylpropenes and to advance regulatory decision making.